HOUSEHOLD EXPENDITURE IN RESPONSE TO NATURAL DISASTERS - Eny Sulistyaningrum (Journal of Indonesian Economy and Business (JIEB), 2015)
Natural disasters have increased in their frequency, and the intensity of their destruction over the last ten years in Indonesia. Households usually respond to these difficulties by cutting their consump-tion, especially for non-essential goods. Arguably natural disasters are exogenous events, so this paper uses the exogenous variation from natural disasters as a natural experiment design to estimate the effect of disasters on household expenditure. When a certain group is exposed to the causal variable of interest, such as a disaster, and other groups are not, the Difference In Difference model (DID) can be used for estimation. Using a micro level survey data set from the Indonesian Family Life Survey (IFLS) which covers approximately 83 percent of the Indonesian population within the survey area, this paper examines the effects of natural disasters on household expenditure. This paper also examines whether there are any different impacts from different types of disasters. The finding is there are no significant effects of disasters on total household expenditure for households living in disaster regions, whether they are affected directly or not by the disaster.Keywords: natural disasters, household expenditure, DID, natural experiment